Comparative Whey Proteome Profiling of Donkey Milk With Human and Cow Milk - Zhang, Xinhao; Jiang, Guimiao; Ji, Chuanliang; Fan, Zhaobin; Ge, Shihao; Li, Haijing; Wang, Yantao; Lv, Xin; Zhao, Fuwei (Frontiers in Nutrition, 2022)
Donkey milk (DM), similar to human milk (HM) in compositions, has been suggested as the best potential hypoallergenic replacement diet for babies suffering from cow milk (CM) protein allergens. Despite advances in proteomics technologies, studies of the DM whey proteome are relatively sparse. In this study, label-free quantitative proteomic approach was conducted to quantitatively identify the differentially expressed whey proteins (DEPs) in DM vs HM group and DM vs CM group. In total, 241 and 365 DEPs were found in these two groups respectively. DEPs were then subjected to intensive bioinformatic analysis. Results revealed that the majority of DEPs participated in lipoprotein metabolic process, regulation of cytokine production, chemical homeostasis and catabolic process. Kyoto Encyclopedia of Gene and Genomes (KEGG) pathways analysis found that these DEPs mainly participated in antigen processing, complement and coagulation cascades. These results may provide valuable information in the composition of milk whey proteins in DM, HM and CM, especially for low abundant components, and expand our knowledge of different biological functions between DM and HM or CM.